Enzyme linked oligonucleotide assay for the sensitive detection of SARS-CoV-2 variants - Shola David, Michael; Kanayeva, Damira (Frontiers in Cellular and Infection Microbiology, 2022)
The exponential spread of COVID-19 has prompted the need to develop a simple and sensitive diagnostic tool. Aptamer-based detection assays like ELONA are promising since they are inexpensive and sensitive. Aptamers have advantages over antibodies in wide modification, small size, in vitro selection, and stability under stringent conditions, which aid in scalable and reliable detection. In this work, we used aptamers against SARS-CoV-2 RBD S protein to design a simple and sensitive ELONA detection tool. Screening CoV2-RBD-1C and CoV2-RBD-4C aptamers and optimizing assay conditions led to the development of a direct ELONA that can detect SARS-CoV-2 RBD S glycoprotein in buffer solution and 0.1 % human nasal fluid with a detection limit of 2.16 ng/mL and 1.02 ng/mL, respectively. We detected inactivated Alpha, Wuhan, and Delta variants of SARS-CoV-2 with the detection limit of 3.73, 5.72, and 6.02 TCID50/mL, respectively. Using the two aptamers as capture and reporter elements, we designed a more sensitive sandwich assay to identify the three SARS-CoV-2 variants employed in this research. As predicted, a lower detection limit was obtained. Sandwich assay LOD was 2.31 TCID50/mL for Alpha, 1.15 TCID50/mL for Wuhan, and 2.96 TCID50/mL for Delta. The sensitivity of sandwich ELONA was validated using Alpha and Wuhan variants spiked in 0.1 % human nasal fluid sample condition and were detected in 1.41 and 1.79 TCID50/mL LOD, respectively. SEM was used to visualize the presence of viral particles in the Delta variant sample. The effective detection of SARS-CoV-2 in this study confirms the potential of our aptamer-based technique as a screening tool in preventing the further spread of SARS-CoV-2.